2020
DOI: 10.1097/j.pain.0000000000001984
|View full text |Cite
|
Sign up to set email alerts
|

Offset analgesia identifies impaired endogenous pain modulation in pediatric chronic pain disorders

Abstract: Offset analgesia (OA), a psychophysical test of endogenous pain inhibition, is diminished in many adult chronic pain disorders but OA has not been investigated in youth with chronic pain disorders. This study assessed OA responses in 30 youth with chronic primary and secondary pain disorders and 32 healthy controls. The OA, control, and constant thermal tests were evoked with an individualized noxious heat stimulus of approximately 50/100 mm on a visual analogue scale followed by 1°C offset temperature. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…These features can be associated with each other, but causative relations cannot be deduced from the present study. PA and OA reflect the function of endogenous pain inhibition mechanisms (D’Agata et al, 2015; Shulman et al, 2020; Zhang et al, 2018), the alterations of which – owing to MS‐lesions – may contribute to enhanced activity and reactivity of spinal nociceptive neurons, hence to centrally mediated hyperalgesia (Campbell & Meyer, 2006). Hyperalgesia can also result from sensitized nociceptors (Treed et al, 1992; Woolf, 2011), which in MS may occur due to secondary consequences of the disease, including poor posture and/or balance, muscle weakness and muscle spasm (Brola et al, 2014; Truini et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features can be associated with each other, but causative relations cannot be deduced from the present study. PA and OA reflect the function of endogenous pain inhibition mechanisms (D’Agata et al, 2015; Shulman et al, 2020; Zhang et al, 2018), the alterations of which – owing to MS‐lesions – may contribute to enhanced activity and reactivity of spinal nociceptive neurons, hence to centrally mediated hyperalgesia (Campbell & Meyer, 2006). Hyperalgesia can also result from sensitized nociceptors (Treed et al, 1992; Woolf, 2011), which in MS may occur due to secondary consequences of the disease, including poor posture and/or balance, muscle weakness and muscle spasm (Brola et al, 2014; Truini et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory testing then commenced following a training session. Testing included: (1) the measurement of warm sensation threshold and cold sensation threshold, as indicators of spinothalamic conduction (Willis & Westlund, 1997); (2) mechanical detection threshold, as an indicator of the dorsal column/medial lemniscal conduction (Noback et al, 2012); (3) the thermal grill illusion, as an indicator of central integration of thermal pathways and pain (Craig & Bushnell, 1994; Jutzeler et al, 2017); and (4) pain adaptation and offset analgesia, as indicators of central pain inhibition (D’Agata et al, 2015; Shulman et al, 2020). Testing was done in a random order.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, this standard 3-temperature paradigm has not been tested in a MRI setting with a pediatric population; however, OA was assessed in youth with chronic pain one time (outside MRI), applying an individualized noxious thermal stimulus of 50/100 on a VAS. 37 Using a thermal stimulator which is placed in contact with the skin, a preset computer-controlled temperature paradigm delivers the specific temperature pattern with the subject rating their pain in real time. A response to this dynamic test stimulus or offset trial ( Figure 1A ) consists of a reduction in self-reported pain intensity when the test temperature is applied for 5 seconds, raised by 1°C for 5 seconds, reduced by 1°C, and held for 20 seconds.…”
Section: Offset Analgesia In Experimental Settingsmentioning
confidence: 99%
“…Recent studies report decreased or absent OA responses in patients with fibromyalgia, 38 neuropathic pain, 17 migraine, 39 and chronic pain of various etiologies. 36 , 37 , 40 In addition, three studies focusing only on chronic patients indicated decreased OA responses in patients with diabetic polyneuropathy, knee osteoarthritis, 19 and chronic radicular pain 17 , 18 , 20 although there was large interindividual variation. In patients with chronic pain, the attenuation of OA effects was observed by delayed offset and a relatively minor decrease in pain scores following the 1°C decrease in temperature as opposed to the disproportionately large reduction in pain perception among healthy controls ( Figure 1 ).…”
Section: Offset Analgesia As a Clinical Toolmentioning
confidence: 99%
“…One proposed mechanism for the presence of these atypical sensory sensitivities in adult headache patients is central sensitization of the nervous system [7,8]. Importantly, recent evidence does support the presence of central sensitization in youth with chronic headaches [9,10].…”
Section: Introductionmentioning
confidence: 99%